Corporate Governance Practices and Sustainable Business Models in India - Tripathi, Shailja; Shukla , Hitesh; Srivastava , Ankita (International Journal of Accounting and Economics Studies, 2025)
In the Indian business climate, a great deal of emphasis has been paid to the changes in corporate governance and sustainable business models. The objective of this study is to present a thorough examination of the relationship that exists between the implementation of sustainable business models and its corporate governance practises. The report starts by explaining how corporate governance is changing in India while considering recent legal changes and industry-specific best practices. It looks at how different governance frameworks affect Indian firms’ stakeholder engagement tactics, accountability frameworks, and decision-making procedures. The research provides many facets of corporate governance and sustainable business models in India by drawing on a wide variety of case studies and empirical data. It points out areas that need development and showcases examples of excellent practises. The research also looks at how important stakeholders, such as regulators, shareholders, and civil society, corporate governance and sustainability programmes develop. It looks at cooperative efforts needed to create an atmosphere to ethical business practises and sustainable growth. In the end, our study adds to the larger conversation on sustainable business practises and corporate governance by providing insightful information to academics, investors, corporate executives, and legislators in Indian context.